2015
DOI: 10.1007/s00705-015-2618-5
|View full text |Cite
|
Sign up to set email alerts
|

Biology and management of sugarcane yellow leaf virus: an historical overview

Abstract: Sugarcane yellow leaf virus (SCYLV) is one of the most widespread viruses causing disease in sugarcane worldwide. The virus has been responsible for drastic economic losses in most sugarcane-growing regions and remains a major concern for sugarcane breeders. Infection with SCYLV results in intense yellowing of the midrib, which extends to the leaf blade, followed by tissue necrosis from the leaf tip towards the leaf base. Such symptomatic leaves are usually characterized by increased respiration, reduced photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 79 publications
0
22
0
Order By: Relevance
“…Many viruses belonging to Luteoviridae can also induce purple coloration symptoms on their host plants. For instance, TuYV, which is widespread in European countries, induces reddening/purpling of the leaves on oilseed rape 64 ; reddish tinge can be found on some Sugarcane yellow leaf virus -infected sugarcane cultivars 65 ; and the red leaf disease on oats and maize is caused by a luteovirus called Barley yellows dwarf virus 66 , 67 . Here, we showed that the transformation of the BrYV amplicon can induce purple leaf symptoms on transgenic Arabidopsis plants.…”
Section: Discussionmentioning
confidence: 99%
“…Many viruses belonging to Luteoviridae can also induce purple coloration symptoms on their host plants. For instance, TuYV, which is widespread in European countries, induces reddening/purpling of the leaves on oilseed rape 64 ; reddish tinge can be found on some Sugarcane yellow leaf virus -infected sugarcane cultivars 65 ; and the red leaf disease on oats and maize is caused by a luteovirus called Barley yellows dwarf virus 66 , 67 . Here, we showed that the transformation of the BrYV amplicon can induce purple leaf symptoms on transgenic Arabidopsis plants.…”
Section: Discussionmentioning
confidence: 99%
“…However, to date, M . sinensis has not been reported to be a host for ScYLV [ 10 ]. For further diagnostic testing, total RNA was re-extracted and subjected to HTS and bioinformatics analysis.…”
Section: Resultsmentioning
confidence: 99%
“…ScYLV is a causal agent of yellow leaf syndrome in sugarcane, which is characterized by yellowing of the leaf midrib on the abaxial surface, and accounts for yield losses of 11–50% [ 10 ]. ScYLV is spread in a persistent, circulative, and non-propagative manner by several aphid species, notably by Melanaphis sacchari and R .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations